2002
DOI: 10.1046/j.1440-1746.2002.02666.x
|View full text |Cite
|
Sign up to set email alerts
|

Reinfection rate following effective therapy against Helicobacter pylori infection in Japan

Abstract: The reinfection rate after eradication of H. pylori is low in Japan despite the country's high prevalence of H. pylori infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 22 publications
3
23
0
Order By: Relevance
“…Others [32] have reported a higher H. pylori reinfection rate in Japan (2.0% per year) than we have found previously [21] and in the present study. We cannot readily explain these differences.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Others [32] have reported a higher H. pylori reinfection rate in Japan (2.0% per year) than we have found previously [21] and in the present study. We cannot readily explain these differences.…”
Section: Discussionsupporting
confidence: 52%
“…We previously reported that the reinfection rate with H. pylori in this population was low (\0.8% per patient year) despite the high prevalence of infection [21]. However, in that study, several factors could have led to misleading results.…”
Section: Introductionmentioning
confidence: 71%
“…Our PubMed search yielded 10 studies of H. pylori recurrence conducted in developed countries [4][5][6][7][8][9][10][11][12][13], and 7 studies conducted in developing countries [14 -20] that used the 13 CUBT at eradication and follow-up and otherwise met our inclusion criteria. Table 1 summarizes the studies from the developed countries, and Table 2, the studies from the developing countries.…”
Section: Resultsmentioning
confidence: 99%
“…3 for the developed countries [4,6,7,[10][11][12][13], and in Fig. 4 for the developing countries [16,17,19,20].…”
Section: Resultsmentioning
confidence: 99%
“…We have reported results on several important medical issues in these patients [15][16][17][18][19][20][21][22]. Most importantly, the eradication of H. pylori in patients with peptic ulcer diseases in whom the cancer was not yet established reduced their risk of developing gastric cancer to approximately one-third.…”
mentioning
confidence: 99%